Difficulties in Printed Modular Distance Learning: Scale Development and Psychometric Properties - Calaguas, Glenn Medallon; Manarang, Noel Calma; Cortez, Aina Pangan; Mercado, Riza Manalo (Jurnal Pendidikan Progresif, 2023)
This study focused on the development of a scale that can be used to identify difficulties in printed modular distance learning from the perspective of learners. Extant literature was analyzed, and 20 learners were interviewed aimed at identifying difficulties. Insights from both literature and interviews served as the basis for the writing of 23 items on the initial scale, distributed under seven themes. Ten learners were asked to participate in the trial run, and 619 learners participated in the test administration. With responses during the test administration, means and standard deviations were computed, and scale reliability was evaluated using Cronbach’s Coefficient Alpha formula, while factor analysis was used to evaluate scale validity. Six factors were retained after factor analysis. The scale developed is psychometrically sound and can identify difficulties in printed modular distance learning, as can be observed from the results of its reliability and validity evaluation. Keywords: distance learning, modular learning, scale developmentDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202333